ANALISIS PERBANDINGAN MAKNA AIR DAN API DALAM PERIBAHASA MANDARIN DAN BAHASA INDONESIA - Megawati, Megawati; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractChinese idioms are words or phrases arranged in a certain arrangement, the meaning of which cannot be directly explained from the meaning of the constituent words. Indonesian idioms are of from the language expression with a very clear meaning, including the norms, counsel, principles, beharviors andvalues of peoples lives and society. Unlike Chinese, are not fixed. The researchprupose of the article is to focus on the emotional color of Chinese and Indonesian idioms with waterand fire and analyze their similiarities and differences. The research result show that most Indonesian and Chinese idioms have the same meaning, but their difference is that Indonesian idioms containing the word water arerarely used to express the power of water or the surrounding environment. Idioms containing the word water in Chinese arerarely used to describe things. The difference is that indonsian idioms containing the fire morpheme are rarely used express fire, war, flames, primitive farming techniques, emergency situations, hot weather, and certain actions. Chinese idioms containing the word fire are rarely used to describe things or people.Keywords: Chineses Proverbs, Comperative Analyse, Indonesians Proverbs, Water and Fire Proverbs